2010
DOI: 10.4097/kjae.2010.58.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Growth suppression of four cancer cells by hyperbaric nitrous oxide and methotrexate

Abstract: BackgroundNitrous oxide concentration is easily controlled by respiratory ventilation. It suppresses bone marrow via the inhibition of thymidylate synthesis. The aim of this work was to determine the optimal pressure and exposure duration of nitrous oxide, as well as methotrexate concentration that maximizes the suppression of 4 cancer cells: CCRF-CEM, K562, A549 and MDA-MB-231.MethodsEach cancer cell was cultured in a hyperbaric chamber at 1, 2 and 3 atmosphere of 74% nitrous oxide for 24, 48, and 72 hours at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Also the growth suppression of leukemic cells by hyperbaric nitrous oxide for a longer time has been studied [33]. An in vitro study with 4 cancer cell-lines (CCRF-CEM, K562, A549 and MDA-MB-231) demonstrated that administration of N 2 O at hyperbaric pressures made not difference [34].…”
mentioning
confidence: 99%
“…Also the growth suppression of leukemic cells by hyperbaric nitrous oxide for a longer time has been studied [33]. An in vitro study with 4 cancer cell-lines (CCRF-CEM, K562, A549 and MDA-MB-231) demonstrated that administration of N 2 O at hyperbaric pressures made not difference [34].…”
mentioning
confidence: 99%